Primary Productivity Levels and About Phythoplankton In Tamblingan Lake - Simanjuntak, Jordan Alexander Anggiat; Restu, I Wayan; Kartika, I Wayan Darya (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
The role of lake waters in supporting people's lives in a broad sense is largely determined by the level of lake productivity, one of which is primary productivity. The primary productivity of the lake can be seen from the abundance and diversity of phytoplankton which are the basic components in the food chain system in waters. The purpose of this study was to determine the level of primary productivity and abundance of phytoplankton. The bottle-dark-bottle-light method was used to determine the photosynthetic rate and respiration of phytoplankton. Gross photosynthesis (GP = dirty photosynthesis) is obtained by subtracting the dissolved oxygen content in the dark bottle from the dissolved oxygen content in the light bottle, after being subjected to lighting (incubation) for several hours. Result the highest abundance is at station II. The uniformity index shows that for station 3 it is the lowest category. The results of the calculation of the phytoplankton dominance index have a value that is inversely proportional to diversity. Based on the category, the index value for the three stations is categorized as low dominance. Water quality parameters measured include dissolved oxygen (DO), degree of acidity (pH), temperature, brightness, and turbidity. Based on all measurements and several aspects of conditions that occur in the waters of Lake Tamblingan, it is still classified as normal and good enough for the continuation of aquatic life. The determinant of the primary productivity among them was pH, temperature, turbidity, and brightness.